Compton scrattering study using ludlum configuration for tissue-equivalent phantom material made from soy-lignin bonded Rhizophora spp. particleboard - Siti Hajar Zuber; Muhammad Fahmi Rizal Abdul Hadi; Oluwafemi, Samson Damilola; Mohd Fahmi Mohd Yusof; Nurul Ab. Aziz Hashikin; Mohd Zahri Abdul Aziz; Rokiah Hashim; Norriza Mohd Isa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rhizophora spp. particleboards were prepared at approximately (20.0 × 20.0 × 1.0) cm3 and at 1.0 g·cm-3 target density. The mass attenuation coefficient of the soy-lignin bonded Rhizophora spp. particleboard was measured by Compton scattering using Ludlum configuration utilizing the Cesium-137 (137Cs). Monte Carlo (MC) GATE code was employed to simulate the scattering by using the same set-up. Compton scattering results from both experimental and simulation methods were compared with XCOM value of water. Half value layer (HVL) and mean free path (MFP) were calculated and analyzed. For Compton scattering method in comparison to XCOM value of water, both non-coated and coated samples showed a statistically non-significant value with p-value more than 0.05. The overall results suggested that the mass attenuation coefficient, HVL and MFP of soy-lignin bonded Rhizophora spp. particleboard based on Compton scattering study is within close agreement with XCOM value for water, exhibiting its potential as phantom materials.